Ethical Disputes over Living Organ Transplant and the Applicable Solutions to These Disputes in China - Yang, Tongwei; Wu, Yijin (Acta Bioethica, 2018)
Objectives: In this study, we examine the ethical issues concerning living organ transplant in China. We attempt to review and analyze the ethical disputes that the living organ transplant faces in China and try to find applicable solutions to these disputes. Design: Ethical Analysis. Setting: Living organ transplant in China. Results: The ideal approaches to solving the ethical disputes involve (1) preventing disease, strengthening physical fitness, and improving the health of the national citizen; (2) encouraging the citizens to donate their organs after death; and (3) developing new technologies for organ transplant. Realistic approaches to addressing the ethical disputes over the living organ transplant include choosing the lesser of two evils, reducing the harm to the donor as much as possible and improving the transplant quality. Conclusions: The living organ transplant in China is an expedient measure instead of an ideal option and should be conducted under strict laws and regulations.